Identificação de áreas aptas ao aproveitamento de fontes renováveis de energia elétrica a partir da viabilidade econômica em áreas fragilizadas - Peres, Kelly Krampe (2022)
Brazilian energy matrix is predominantly dependent on water resources. With the insistent water crisis, water cannot be considered an inexhaustible good. Thus, other sources should be explored, such as wind and solar energy. This paper aimed to collect data regarding the implementation of a wind system with a view to recovering fragile areas, to allow natural regeneration or through reforestation of the degraded environment, in the city of Cascavel, in the western region of Paraná. To prepare the slope maps, geomorphometric data from Brazil available on the INPE website were taken. For the soil class and texture map, data from EMBRAPA from the “Map of soil use of the state of Paraná” were used. For the use and coverage of the soil, images from the Sentinel Program were used. Regarding the climate, the Köppen classification was used. For the maps of environmental fragility, maps of geoenvironmental characterization were used (slope, climate, soil class and texture, and land use and occupation) based on some studies. The verification of the riparian forest was based on the Brazilian Forest Code Law 12651/2012. For the study of the local wind potential, hourly data from SIMEPAR were used, using the frequency curve and Weibull distribution. In order to carry out the economic feasibility, data were collected regarding the acquisition (turbine, tower), installation (foundation and civil works), maintenance of the wind turbine, among others. The main results found indicate that the IRR and NPV values for 7,10,15 and 20 years were negative, a discounted Payback of 51 years and 8 months was found, which becomes unfeasible, considering that the useful life of the wind turbine is of 20 years. The city of Cascavel (Rio Cascavel watershed) has a little steep slope, Latosol predominance, land use and occupation predominantly agricultural with large urban areas, intermediate fragility. Average wind speed in 30 meters is 5.08 m/s, the wind turbine chosen was the Wes 50, which generates 9,762.39 kWh/month in Cascavel, the location chosen for the installation of the wind turbine was a fragile region near from a quarry. This project was considered economically unfeasible. However, due to such social, energy and environmental importance, it is necessary to think of ways to make it viable, through existing environmental policies (payment for environmental service and carbon credits), as well as through more efficient public policies, aimed at the environment and improving the quality of life of rural residents.